Dating Methods of Pleistocene Deposits and Their Problems: VI. Paleomagnetism - Barendregt, R. W. (Geoscience Canada, 1981)
Paleomagnetism is used in Pleistocene stratigraphic studies as a tool for correlation and relative age dating of equivalent strata or for the absolute dating of deposits. The method is based on the detection of changes in the earth’s magnetic field and especially changes of polarity that are recorded by ferromagnetic sediments at the time of deposition. The study of paleomagnetism as a geophysical dating method began in the1960s and has grown geometrically since. Instrumentation has greatlyi mproved and the statistical analysis of data, so essential to the proper interpretation of the magnetic record, would not have been possible without computer facilities. Fine-grained sediments and lava flows are the two media most frequently used. Because reversals have occurred repeatedly in the past, their identification within incomplete sedimentary records is only possible through comparison with other stratigraphic or radiometric data collected for similar or related sedimentary sequences. Continuously deposited marine or terrestrial sediments which show a high sedimentation rate provide isochrons which can be used for world-wide correlation. The recent flourish of research activity into the secular variation of the earth’s non-dipole field promises to greatly refine and embellish the geomagnetic time table for the Pleistocene.